2005
DOI: 10.1074/jbc.m414443200
|View full text |Cite
|
Sign up to set email alerts
|

LGR8 Signal Activation by the Relaxin-like Factor

Abstract: The relaxin-like factor (RLF) is thought to be responsible for the intra-abdominal migration of the testis during mammalian development. Our latest studies of RLF and LGR8 have revealed that the N-terminal region of the A chain is not required for receptor binding but is indispensable for cyclic AMP generation. RLF derivatives with six residues deleted from the N terminus of the A chain are active, whereas further truncation, up to the first A chain cysteine (A-10), yields tightly binding ligands devoid of sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
102
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(109 citation statements)
references
References 22 publications
6
102
0
1
Order By: Relevance
“…The N terminus of the A-chain of H2 relaxin has no functional role as reported previously (19,20). Shortening of the N terminus of the A-chain of porcine (19,20) or H2 (21) relaxin by up to four residues had no effect on binding or activation of RXFP1 and RXFP2.…”
Section: A17mentioning
confidence: 53%
See 4 more Smart Citations
“…The N terminus of the A-chain of H2 relaxin has no functional role as reported previously (19,20). Shortening of the N terminus of the A-chain of porcine (19,20) or H2 (21) relaxin by up to four residues had no effect on binding or activation of RXFP1 and RXFP2.…”
Section: A17mentioning
confidence: 53%
“…These findings in turn, suggested that no single amino acid in the N-terminal region of the A chain is functionally important, but that the presence of an ␣-helix is required to maintain the overall fold of the protein which is key to the H2-RXFP1 and H2-RXFP2 interactions (21). In contrast, a similar truncation study on INSL3 showed that it can be truncated at the N terminus of its A-chain by up to nine residues without affecting the binding affinity to its receptor RXFP2, while becoming a high affinity antagonist (22). Thus, H2 relaxin is binding to and activating both RXFP1 and RXFP2 receptors in a similar manner but via a mechanism that is different compared with INSL3 (21).…”
Section: A17mentioning
confidence: 95%
See 3 more Smart Citations